1996
DOI: 10.1093/brain/119.4.1221
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral organization of component processes in reading

Abstract: The cerebral organization of word identification processes in reading was examined using functional magnetic resonance imaging (fMRI). Changes in fMRI signal intensities were measured in 38 subjects (19 males and 19 females) during visual (line judgement), orthographic (letter case judgement), phonological (nonword rhyme judgement) and semantic (semantic category judgement) tasks. A strategy of multiple subtractions was employed in order to validate relationships between structure and function. Orthographic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
368
5
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(444 citation statements)
references
References 0 publications
62
368
5
5
Order By: Relevance
“…These activation patterns are consistent with a number of previous investigations in healthy young subjects comparing words to nonwords or to nonverbal stimuli (e.g., tones or letter strings) [Davis et al, 2004;Fiebach et al, 2002;Price et al, 2003]. Moreover, these areas are also activated during judgment tasks that specifically target semantic processing for verbal or nonverbal stimuli [Binder et al, 1997;Demonet et al, 1994;Pugh et al, 1996;Simos et al, 2002]. In summary, increased cerebral activity in the angular gyrus, inferior temporal gyrus, posterior middle temporal gyrus, and inferior prefrontal gyrus is consistent with the activation of semantic representations, regardless of stimulus modality.…”
Section: Cortical Activation For Lexicosemantic Representations In Adsupporting
confidence: 90%
“…These activation patterns are consistent with a number of previous investigations in healthy young subjects comparing words to nonwords or to nonverbal stimuli (e.g., tones or letter strings) [Davis et al, 2004;Fiebach et al, 2002;Price et al, 2003]. Moreover, these areas are also activated during judgment tasks that specifically target semantic processing for verbal or nonverbal stimuli [Binder et al, 1997;Demonet et al, 1994;Pugh et al, 1996;Simos et al, 2002]. In summary, increased cerebral activity in the angular gyrus, inferior temporal gyrus, posterior middle temporal gyrus, and inferior prefrontal gyrus is consistent with the activation of semantic representations, regardless of stimulus modality.…”
Section: Cortical Activation For Lexicosemantic Representations In Adsupporting
confidence: 90%
“…Similarly, we propose that the lack of connectivity between the VWFA and the left inferior frontal gyrus may be linked to their inability to successfully engage this region during phonological processing of written words (e.g. (Poldrack et al, 1999;Price, 2000;Pugh et al, 1996). This link between connectivity and reading performance is consistent with the finding that connectivity may increase after effective treatment, as shown by Richards et al (2008).…”
Section: Accepted M Manuscriptsupporting
confidence: 82%
“…Neuroimaging studies have observed pLIPC activation during tasks requiring analysis of phonological representations [32,34,55], such as rhyme and syllable judgments. Moreover, activation in pLIPC has been reported during tasks involving visually presented nonwords [35], with initial evidence suggesting that greater pLIPC activation is observed during phonological processing of novel (e.g. pseudo-English) relative to familiar (e.g.…”
Section: Introductionmentioning
confidence: 99%